Tunnelless totally implantable venous access device implantation via ultrasound-guided axillary vein puncture: A retrospective analysis - Haiguan Luo; Yuying Pan; Shuchen Zhu; Lihui Huang; Mingyan Dong; Qiaohong Zhang; Yicui Piao (Journal of International Medical Research)
Objective This study aimed to assess the feasibility and safety of using the ultrasound-guided axillary vein puncture technique to implant the totally implantable venous access device without a tunnel. Methods This study retrospectively analyzed data from 703 patients who underwent totally implantable venous access device implantation in the chest wall between January 2022 and March 2023. Ultimately, 685 patients underwent tunnelless totally implantable venous access device implantation via ultrasound-guided axillary vein puncture. We collected data regarding the patients’ age, sex, body weight, body mass index, axillary vein diameter, depth of the axillary vein from the body surface, surgical success rate, operation duration, and postoperative follow-up. Results Of the 703 patients who signed the consent forms for totally implantable venous access device implantation, 685 were included in the axillary vein puncture group. The follow-up period ended on 31 August 2023; the mean follow-up duration was 281.59 days. The following complications were observed: catheter retrograde to the internal jugular vein in seven patients, catheter occlusion in three patients, catheter-related infections in two patients, catheter-related vein thrombosis in two patients, and skin infection around the infusion port in one patient. The overall immediate and long-term complication rate was 2.13%. Conclusion The tunnelless totally implantable venous access device implantation technique via ultrasound-guided axillary vein puncture offers a highly effective, safe, and aesthetically pleasing alternative for chest wall totally implantable venous access device implantation.